Radiological aspects in the diagnosis of pneumonia: A literature review (Research, Society and Development, 2023)
Introduction: Pneumonia is an infection that settles in the lungs, which can affect the pulmonary alveoli where the terminal branches of the bronchi and interstices flow. They are caused by the penetration of an infectious agent such as bacteria, viruses, fungi and by allergic reactions in the alveolar space, where gas exchange occurs. Objective: To identify radiological findings that could be associated with pneumonia. Materials and Methods: This is an integrative review of the literature on the new evidence that justifies the radiological findings of pneumonia. In addition, information was cross-referenced in the National Library of Medicine, Scientific Electronic Library Online, Google Scholar and Virtual Health Library databases. Results and Discussion: Accurate diagnosis of pneumonia is important to ensure effective treatment, as the clinical symptoms of pneumonia may resemble other respiratory conditions, however the combination of anamnesis, physical examination, and imaging tests is essential. Typical radiological features include pulmonary consolidations for common pneumonia and ground-glass opacities for atypical pneumonia, as well as pleural effusion and pulmonary infiltrates common in both cases. Conclusion: Imaging tests, such as chest X-ray and computed tomography, are essential for detecting and monitoring treatment, and the choice between them depends on the severity of the disease. The integration of clinical and radiological information is essential for an accurate diagnosis and an appropriate therapeutic approach in pneumonia. Ultimately, radiological aspects play a crucial role in the diagnostic process of pneumonia.